THE CONCEPT OF CAPITAL INVESTMENTS IN CONSTRUCTION ORGANIZATIONS, THE MAIN TASKS OF THEIR ACCOUNTING - I.Sh.Kabulov; I.B.Sapayev; A.O.Rahimov; A.M.Saparbekov; D.Sh.Toshpo’latova; B.S.Koptileuov; S.A.Alisherova; Sh.S.Abdusaidov (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
Implement five-year regional programs developed in the section of districts and cities for 14 regions , socio-economic development Developing and implementing a program of practical measures for cities and districts with unsatisfactory rating indicators, further improving the urbanization policy to improve the living conditions of the population in the regions, taking measures to transform the cities of Samarkand and Namangan into "cities of millions" in the future, New Reviewing and commissioning the first few areas of Andijan city, increasing the urbanization level of Kashkadaryo region to 50%, introducing the "Usability of Cities" index, which evaluates the comfort of the lifestyle of the people in cities, digitizing cities, improving the quality of construction and design works, and developing them in accordance with the concept of "Smart City" , establishment of innovative educational and production technology park "INNO" established in Tashkent city in 4 regions, creating high added value in districts being transformed into innovative regions mastering innovative product production technologies, combining scientific research conducted in the field of architecture and construction in higher education institutions with practice, technical regulation of the construction industry, fundamentally improving the system of development of urban planning documents of settlements and developing and implementing a program for providing urban planning documents, On the basis of the development of the master scheme of settlement, the construction of more than 19 million square meters of modern housing instead of outdated houses in the cities, and the creation of conditions for the relocation of more than 275 thousand families to new massifs, capital investments are of great importance in achieving these goals.